Online health information seeking behavior among breast cancer patients and survivors: a scoping review - Jialin Chen; Yiwen Duan; Haozhi Xia; Runxi Xiao; Tingting Cai; Changrong Yuan (BMC Women's Health)
Abstract Purpose This scoping review aims to summarize online health information seeking (OHIS) behavior among breast cancer patients and survivors, identify research gaps, and offer insights for future studies. Methods Following Arksey and O’Malley’s framework, we conducted a review across PubMed, Web of Science, CINAHL, MEDLINE, Cochrane, Embase, CNKI, Wanfang Data, and SinoMed, covering literature from 1 January 2014 to 13 August 2023. A total of 1,368 articles were identified, with 33 meeting the inclusion criteria. Two researchers independently screened, extracted, and summarized the data. Results The studies addressed three main themes:OHIS behavior, factors associated with OHIS, and intervention programs on OHIS. Key information sources included national or nonprofit cancer organizations’ websites, search engines, and social media. Commonly sought information involved breast cancer knowledge, treatment options, and prognosis, with information seeking behaviors varying by disease stages. While patients valued the convenience and accessibility of online resources, dissatisfaction was common due to inaccurate or misleading content. Factors such as age, education, income, disease characteristics, and psychological factors significantly influenced OHIS behaviors. Conclusion This review identifies significant gaps in exploring OHIS behavior among breast cancer patients and survivors, highlighting the inadequacy of current interventions. Future research should focus on diverse age groups, refine the language of web-based health information, enhance user comprehension of professional content, and develop tailored information systems for different stages of the health journey.